2020
DOI: 10.29207/resti.v4i4.2156
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Classification of Song Lyrics using Bidirectional LSTM Method with GloVe Word Representation Weighting

Abstract: The rapid change of the music market from analog to digital has caused a rapid increase in the amount of music that is spread throughout the world as well because music is easier to make and sell. The amount of music available has changed the way people find music, one of which is based on the emotion of the song. The existence of music emotion recognition and recommendation helps music listeners find songs in accordance with their emotions. Therefore, the classification of emotions is needed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…This outcome is a result of the exploitation of both lyric and audio data and making one concentrated prediction for each song by its segments. Additionally, in Table 7 we compare our model (BERT + CNN) with other models that utilize the same dataset (MoodyLyrics) as us [ 12 , 46 , 47 , 48 , 49 ]. We should also mention that our final model outperforms previous approaches that use different sources of data, specifically our model achieves 94.32% F 1 Score while Malheiro鈥檚 model [ 14 ] achieves 88.4% F 1 Score .…”
Section: Resultsmentioning
confidence: 99%
“…This outcome is a result of the exploitation of both lyric and audio data and making one concentrated prediction for each song by its segments. Additionally, in Table 7 we compare our model (BERT + CNN) with other models that utilize the same dataset (MoodyLyrics) as us [ 12 , 46 , 47 , 48 , 49 ]. We should also mention that our final model outperforms previous approaches that use different sources of data, specifically our model achieves 94.32% F 1 Score while Malheiro鈥檚 model [ 14 ] achieves 88.4% F 1 Score .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we employ Multi-task setup, using XLNet as the base architecture for classification of emotions and evaluate the performance of our model on several datasets that have been organized by emotional connotations solely based on lyrics. We demonstrate superior performance of our transformer-based approach compared to RNN-based approach [9,2]. In addition, we propose a robust methodology for extracting lyrics for a song.…”
Section: Related Workmentioning
confidence: 89%
“…In recent years the use of pre-trained models like GloVe [32], ELMO [33], transformers [10,37] are fast gaining importance for large text corpus has shown impressive results in downstream several NLP tasks. Authors in [9,2] perform emotion classification using lyrics by applying RNN model on top of word-level embedding. The MoodyLyrics dataset [5] was used by [2] who report an impressive F 1 -score of 91.00%.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered one of the breakthroughs in deep learning. Studies in [5], [6], [7] suggested the Word2Vec approach to extract text features, while others suggested Glove [8]. Nevertheless, both approaches are context-independent, and they could not catch all semantic information such as Out-Of-Vocabulary (OOV) and some opposite word pairs.…”
Section: Introductionmentioning
confidence: 99%